THE EFFECT OF HYPNOSIS THERAPY ON THE PAIN SCALE OF POST OPERATIVE PATIENTS: LITERATURE REVIEW - Wasita, Rangga; Peristiowati, Yuly; Ellina, Agusta Dian; Fajriyah, Asruria Sani (Journal of Public Health Research and Community Health Development, 2023)
Background: Acute pain is a sensory or emotional experience associated with actual or functional tissue damage, with a sudden or slow onset and of mild to severe intensity lasting less than 3 months. Surgical procedures can cause acute pain. The main outcome of nursing interventions related to acute pain is a decrease in the level of pain. One of the non-pharmacologic nursing therapeutic interventions that can reduce pain levels and increase comfort is hypnosis therapy. Purpose: To determine the effect of hypnotherapy on pain scale in postoperative patients. Methods: Scientific articles in English and full texts published in 2002-2020 were identified and then analyzed by PI(E)O (problem; intervention; exposure; comparison; outcome). A total of 3404 articles from the PubMed, Wiley, Science Direct, and Google Scholar databases were identified using the keywords "hypnotherapy" OR "pain". Results: The results of the study found articles that discussed the effect of hypnotherapy on the pain scale. Conclusion: Patients who are given hypnosis will feel relaxed and make their subconscious active so that they can easily accept suggestions and can ignore other stimuli, including pain stimuli. Further research should also be carried out in patients who experience chronic pain.